EFFECT OF ENZYME SUPPLEMENTING AND SOAKING TO THE DIETS OF THE LAYING HENS CONTAINING CORN AND WHAET ON PRODUCTIVE PERFORMANCE - & et al., Al Rubaee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at Poultry Research Station Animal–State Board of Agricultural Research/ Ministry of Agricultural, which included two experiments to study the effect of enzyme supplementing and soaking to the diets of the laying hens containing corn and wheat on productive performance. Three hundred Brown-egg hens (ISA Brown) 40 weeks-old were used in this experiment after introductory period for two weeks. Layer hens distributed randomly to ten treatments with 2 replicates (15 hens per replicate); And fed on diets equal protein and metabolic energy according to the age periods in ISA guide. Treatments were as follows: Treatment 1: Control group (100 % corn).Treatment 2: 100% corn with soaking. Treatment 3 : 100% corn with enzymes. Treatment 4:100% corn with soaking and enzymes. Treatment 5: 33% corn replacement wheat with soaking. Treatment 6 : 33% corn replacement wheat and with enzymes. Treatment 7 : 33% corn replacement wheat with soaking and enzymes. Treatment 8: 66% corn replacement wheat  with soaking. Treatment 9: 66% corn replacement wheat with enzymes. Treatment 10 :66% corn replacement wheat with soaking and enzymes. The results showed a significant differences between treatments in egg production (HD%), egg weight, egg mass and feed conversion ratio. Supplementary enzyme with soaking indicate a  significant increase in productive performance.